First ever report of a bite by Nabis argentinus Meyer-Dür (Hemiptera: Heteroptera: Nabidae) on a human - Cornelis, Marcela Fabiola (2017)
Herein, we described the first ever reported bite of Nabis argentinus Meyer -Dür 1870 on a human. The bite was registered in the locality Santa Rosa La Pampa, Argentina (36°37'29.02"S, 64°17'19.13"W). The insect was not provoked by the victim, and thus, the bite was probably not in self-defense. We therefore concluded that the insect bite the victim because it was searching for sources of hydration.